FUNGSI ESTETIS BAHASA INDONESIA DALAM WACANA CERPEN EMAK INGIN NAIK HAJI KARYA ASMA NADIA - Mohammad Fakhrudin (p-ISSN 2356-0576, 2014)
Abstract: This research aims at describing the estetical function of Bahasa in a short story discourse entitled Emak Ingin Naik Haji (EINH) by Asma Nadia. This research uses qualitative and descriptive approaches. The data are collected using observation technique, that is reading rigorously the Bahasa used in EINH, either in form of narration or in form of characters’ conversation. The narration and conversation suitable with the problem in this research are noted in a data-noting form. The instrument used to provide the data is the researcher himself, equiped by the data-noting form. The data-noting form is saved in the hard disc. Next, the data are analyzed using content-analysis technique, that is the technique used to interpret the content. The results of data-analysis are discussed using informal technique. According to this research, it can be concluded the the Bahasa used in EINH has got estetical function that works efectively as (1) the wrapping of story’s theme and message, (2) the mean to tell the reader how eager Emak to perform hajj, (3) the mean to describe Zein’s feeling toword Emak, (4) the mean to tell the occurance/situation, (5) the mean to illustrate the characters’ personalities, (6) the mean to illustrate the setting to sum up, there is a harmony of Bahasa with its functions, both as the mean to deliver the meaning and as the mean to create estetic. Keyword: bahasa variety, estetical value, estetical function of bahasa   Abstrak: Penelitian ini bertujuan mendeskripsikan fungsi estetis bahasa Indonesia dalam wacana cerpen Emak Ingin Naik Haji (EINH) karya Asma Nadia. Pendekatan yang digunakan dalam penelitian ini adalah kualitatif dan deskriptif. Pengumpulan data dilakukan dengan teknik observasi, yakni dengan membaca secara cermat bahasa Indonesia yang digunakan dalam EINH, baik yang berupa narasi maupun percakapan para tokoh cerita. Narasi dan percakapan yang sesuai dengan masalah yang diteliti dicatat dalam form pencatat data. Instrumen yang digunakan untuk penyediaan data dalam penelitian ini adalah peneliti sendiri, dilengkapi dengan form pencatat data. Form pencatat data disimpan dalam hard disk. Selanjutnya, data tersebut dianalisis dengan teknik analisis isi. Hasil analisis data dipaparkan dengan teknik informal. Dalam penelitian ini disimpulkan bahasa Indonesia dalam EINH berfungsi estetis secara efektif sebagai (1) pembungkus tema dan amanat, (2) media bercerita tentang keinginan Emak yang luar biasa hebatnya untuk naik haji, (3) media bercerita tentang perasaan Zein terhadap Emak, (4) media bercerita tentang peristiwa/ keadaan, (5) media untuk menggambarkan watak tokoh cerita, dan (6) media untuk menggambarkan latar. Ada keharmonisan fungsi bahasa Indonesia sebagai media penyampai makna dan sebagai media pencipta keindahan.   Kata kunci: ragam bahasa Indonesia, nilai estetis, fungsi estetis bahasa Indonesia